PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN ENVIRONMENTAL PERFORMANCE TERHADAP ECONOMIC PERFORMANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sucahyo Heriningsih; Novitasari Saputri (Jurnal Ekonomi Dan Bisnis, 2015)
This research is aimed to examine effect Corporate Social Responsibility(CSR) Disclosure and EnvironmentalPerformance on  Economic Performance.This research used Corporate Social Responsibility Index (CSDI) asmeasure of CSR,  Proper Index as measure of Environmental Performance and Return on Equity (ROE)  asmeasure of Economic Performance. The samples of this research are 11 manufactur firms listed at IndonesianStock Exchange year  2006 until 2009. The research hyphotesis were tested using multiple regression analysis.Result of the analysis showed that corporate Social Responsibility Disclosure have significant effect on economicperformance, but Environmental Performance do not has significant effect on  Economic Performance.Keywords: Corporate Social Responsibility Disclosure, Environmental Performance, Economic Performance